ANALISIS KEMAMPUAN DEFERRED TAX EXPENSE DAN PENERAPAN CORPORATE GOVERNANCE DALAM MENDETEKSI EARNINGS MANAGEMENT (Studi pada Perusahaan Manufaktur yang terdaftar pada Bursa Efek Indonesia periode 2011-2015) - B2091151004, JURIAH (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2017)
The purpose of this study was to examine and obtain empirical evidence of the influence of deferred tax expense and good corporate governance simultaneously effect earnings management . Deferred tax expense is predicted to have the ability in detecting earnings management. Application of the principle of good corporate governance is expected to minimize the practice of earnings management. Earnings management is an interference in company’s financial reporting in order to achieve a certain level of income do to the disagreement between managers with shareholders. Opportunities to distort earnings accrual provides an opportunity for managers top roduse profits in accordance with what he wanted. The sample in this study consisted of 32 manufacturing companies listed on the Indonesia Stock Exchange in 2011-2015 with 160 observation. Samples obtained by purposive sampling method. Statistical methods used to test the hypotheses is multiple linear regression analysis. The test results showed that the deferred tax expense is significant positive effect on earnings management. Good corporate governance is measured using a proxy institutional ownership and foreign ownership significant negative effect on earnings management, while the proportion of independent commissioners and the number of audit committee members no significant negative effect on earnings management. Based on F test obtained a significance level of study variables were below 0.05. Earnings management proxy discretionary accruals are statistically significant at the 5 percent level. This indicates that the deferred tax expense and good corporate governance simultaneous effect on earnings management.Keywords: Earnings Management, Deferred tax expense, Corporate Governance1